Saving the Sowetan : the public interest and commercial imperatives in journalism practice - Cowling, Lesley (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2015)
This thesis examines the complex ways in which notions of the public interest and commercial imperatives intertwine in journalism practice. It does this through a study of the 2004 takeover and relaunch of the Sowetan newspaper, the highest circulation daily in South Africa throughout the 1990s and an institution of black public life. The 'public interest' and 'the commercial' are recurring ideas in journalism scholarship and practice, and the relaunch appeared to be a challenge to reconcile the Sowetan's commercial challenges with its historical responsibility to a 'nation-building' public. However, the research shows that the public/commercial aspects of journalism were inextricably entangled with Sowetan's organisational culture, which was the matrix through which its journalism practice was expressed. Conflict in the organisation over the changes was not simply a contest between commercial realities and the public interest, with journalists defending a responsibility to the public and managers pushing commercial solutions, but a conflict between the culture of Sowetan "insiders" , steeped in the legacy of the newspaper, and "outsiders" , employed by the new owners to effect change. Another conclusion of the research is that commercial "realities" "“ often conceptualised as counter to the public interest "“ are highly mutable. Basic conditions, such as a dependence on advertising, exist. However, media managers must choose from a range of strategies to be commercially viable, which requires risk-taking, innovation and, often, guesswork. In such situations, the 'wall' between media managers and senior editors is porous, as all executives must manage the relationship between business and editorial imperatives. Executives tend to overlook culture as a factor in changing organisations, but I argue that journalism could benefit from engaging with management theory and organisational psychology, which offer ways to understand the specific dynamics of the organisation. Finally, I argue that the case of the Sowetan throws into question the idea that there may be a broadly universal journalism culture. The attachment of Sowetan journalists to their particular values and practice suggests that forms of journalism evolve in certain contexts to diverge from the 'professional' Anglo-American modes. These 'journalisms' use similar terms "“ such as the 'public interest' "“ but operationalise them quite differently. The responsibility to the public is imagined in very different ways, but remains a significant attachment for journalists.
Keywords: Sowetan (Johannesburg, -- South Africa); Journalism -- Economic aspects -- South Africa -- Soweto; Journalism -- Political aspects -- South Africa -- Soweto; Black newspapers -- South Africa -- Soweto; Public interest -- South Africa -- Soweto; Corporate culture -- South Africa -- Soweto; Journalistic ethics -- South Africa -- Soweto; Journalism -- Objectivity -- South Africa -- Soweto